Efeitos de um procedimento de ensino de leitura e de escrita, baseado no paradigma de equivalência de estímulos, sobre o desempenho de um jovem com deficiência intelectual - Fonteles, Verônica Siqueira (2019)
Promising results for teaching of reading and writing have occurred in the application of the technology derived from researches on stimulus equivalence. This study aimed to evaluate a procedure of reading and writing of clauses for a child with intellectual disability, using equivalence paradigm that was applied with the aid of JClic, software that has the proposal of being a tool of game creation and interactive activities. The study participant is 11-year-old male with a suggestive clinical condition of Weaver syndrome and mild intellectual impairment. The procedure was composed of the following phases: (a) evaluation of the child’s initial repertoire; (b) teaching and test of reading and writing relations; (c) test of recombination of words and clauses; (d) final evaluation; and (e) evaluation of the child’s performance 30 days after the intervention was done. The obtained results in the initial evaluation and final evaluation (percentage of correct read and written clauses) allowed establishing the child’s performance in relation to reading and writing, in not only the reading of words and clauses that were taught, but also in emergent reading and writing of clauses with recombined words. It was proven that the procedure is effective to install the reading and writing repertoire